The Mythical Underworlds of Francis Stevens and Daphne du Maurier - Aguirre, Mercedes (Collectanea Philologica, 2021)
This article analyses two stories by women writers (The Heads of Cerberus by Francis Stevens (1952) and The Breakthrough by Daphne du Maurier (1964)), which could both be considered as belonging to the genre of science fiction. These stories do not follow the ‘canonical’ or more popular type of underworld narrative, especially the idea of the katabasis or descent to the underworld and the encounter with the dead, a motif which has often been present in Western culture since classical antiquity and has generated numerous narratives. Rather, they evoke the classical myth of the underworld through the use of certain names (such as Charon and Cerberus) as well as exploring other concepts which coincide with ancient Greek accounts of the topography and inhabitants of the world of the dead, the realm ruled over by Hades.